An enigmatic soft tissue creeping phenomenon: The spontaneous peri‐implant mucosa margin and papilla growth. A retrospective clinical study - Ivo Agabiti; Karol Alí Apaza Alccayhuaman; Yasushi Nakajima; Daniele Botticelli (Wiley, 2021)
Abstract Objectives The aim of the present retrospective study was to evaluate papillae filling rate and buccal margins coronal growth in implant‐supported prostheses which were over‐contoured at the apical buccal third to form a rearmost collar zone, thus mimicking a false root. Material and methods The influence of adjacent elements, teeth, implants, or pontics was examined. One‐hundred and three crowns have been assessed in photographs taken on 61 patients after prosthesis delivering and at last follow‐up (mean 2.8 years). The Jemt index was adopted to evaluate papillae growth at the baseline and follow‐up as follows: 0, absence of papilla; 1, less than half of interdental embrasure height; 2, more than half of interdental embrasure height; 3, fully papilla filled interdental embrasure. Index score 4, papilla hyperplasia was not included. Moreover, the coronal growth (or recession) of buccal mucosa in implant‐supported crowns was assessed. Results At baseline, a total of 29 papillae had a 0 score, while only two scored 3 with complete papilla formation. On follow‐up, only one papilla scored 0, while 46 scored 3 with complete interdental embrasures filling. The highest papilla score was registered from first year crown insertion and likewise in interdental embrasures located between two implants or implants and pontics. Moreover, the buccal margin growth was observed in almost 80% of crowns. Such findings seem to indicate that buccal margin and papilla around implant‐supported crowns presented a coronal growth over time, especially during its first year. The average papilla growth between two implants was no lower than that observed in papilla present between implants and natural teeth. Conclusions Recessed areas at collar of implant‐supported prostheses appear to positively influence papillae and buccal margin growth, especially in its first year. Papilla growth between two implants was similar to that observed between implants and natural teeth.